Mengubah Sampah Menjadi Berkah: Pengabdian Masyarakat Di Desa Bandongan Dengan Pengelolaan Bank Sampah Barokah - Mulyadina, Arifah (Jurnal Bina Desa, 2024)
Community service initiative in Bandongan Village through the management of Barokah Waste Bank, which aims to transform waste into a source of economic and environmental benefits. This program implements a comprehensive waste management system, including sorting, weighing, composting, and recycling. By involving active community participation, Barokah Waste Bank has succeeded in reducing the volume of waste disposed of in landfills. This study shows that innovative and participatory waste management not only addresses environmental problems but also creates significant social and economic value, making it a model that can be applied in other villages.